Plantas medicinais como tema gerador de uma proposta interdisciplinar - Tides, Jean (2016)
This study aimed to raise new methodologies in interdisciplinary education in the state school Monteiro Lobato in Dois Vizinhos - PR, using interdisciplinarity in teaching medicinal plants in the disciplines of science, history, geography, mathematics and arts in the program classes more education 1 and 2. the work was carried out through an action research, initially collected data through questionnaires with closed and open questions concerning the reality of the students and the teaching-learning methodology in school Monteiro Lobato. Data were tabulated and analyzed. In the analysis, it was taken into consideration the problem of interdisciplinary education and hence of medicinal plants in school teaching-learning process. While that makes the process of critical analysis suggested and presented activities that contributed to the involvement and construction of interdisciplinary knowledge in the field of agricultural science through theoretical and practical workshops. Among the suggested actions and carried out in the teaching-learning process are the construction of the human body clock (medicinal garden) and preparation of the booklet through the rescue of the popular knowledge acquired with the family of the students, highlighting the importance of the use of medicinal plants . In conclusion we obtain a high level of gain knowledge of medicinal plants, popular knowledge and traditional as well as the effective realization of interdisciplinary teaching, showing the importance of teaching of medicinal plants within schools, contributing to the technical-scientific knowledge and vivencias learners.